Assessment of drought in Izmir district using standardized precipitation index - Mersin, Denizhan; Gülmez, Ayşe; Safari, Mir Jafar Sadegh; Vaheddoost, Babek; Tayfur, Gökmen (My University, 2021)
Droughts are one of the major concerns associated with agro-food and socio-economical security in the World. The continuously changing climate regardless of its cause and effect pushes the limit of the water deficit to the limits. Izmir is a raising city of Turkey that owns various water resources including but not limited to seashores, lakes, river streams, and groundwater reserves. Therefore, the assessment of the historical and future drought events and their potential effect on these water resources is important in the planning and development of the region. In this respect, this study aims to evaluate the historical droughts across İzmir District. For this, monthly precipitation time series in three meteorological stations recorded between 1973-2020 related to the Küçük Menderes basin is used. First, the consistency, randomness, and trend in the time series are investigated using the double mass curve, run test, and linear trend analysis, respectively to ensure the credibility of the posterior drought analysis. Next, the standardized precipitation index (SPI) together with the moving average (MA) operator is used to evaluate the historical deficit associated with meteorological (SPI-1), agricultural (SPI-3), and hydrological (SPI-6 and SPI-12) droughts within a year. It is concluded that there is no permeant drought occurred during the study period, while there are some extreme events in the past that should be evaluated separately. Results also showed that the severity of drought increases from the seashore toward the land.
Bildiri - Yayımlanmış
Bildiri - Kongre ve Sempozyum
Keywords: Hydrology; Drought; Civil engineering; Water resources